Early phase Vogt-Koyanagi-Harada Disease in Nepalese Elderly woman: A case report - Thapa, Bikram Bahadur; Gurung, Shanti; Singh, Sweta; Aryal, Mahesh (Nepalese Journal of Ophthalmology, 2020)
Introduction: Vogt–Koyanagi–Harada (VKH) disease is defined as an autoimmune disorder characterized by bilateral granulomatous panuveitis with systemic manifestations, such as tinnitus, vertigo, and meningism caused by melanocyte antigen-reactive T-cells. Majority of VKH patients present at the age between 20 and 50 years. VKH is uncommon in elderly and challenging to manage. VKH is one of the important differential diagnosis of bilateral pan uveitis Case: A 65 year/ female brought with chief complaint of sudden loss of vision in both eyes, headache and hearing problem for 1 month. She didn’t give any history of other systemic illness, ocular surgery, ocular trauma, chronic use of medicament. Her visual acuity was hand movement with accurate projection of rays (HM) in both eyes The intraocular pressure (IOP) was 12mmHg in both eye. Slit-lamp bio microscopy revealed features of Pan uveitis in both eye. Systemic work up revealed no any other abnormalities. A diagnosis of early phase VKH was made and treated with intravenous pulse steroid therapy followed by tapering dose of oral steroid along with immunemodulator resulting in a very good visual recovery. Conclusion: VKH can present in elderly. immunomodulator should be considered in elderly to prevent side effect of steroid along with recurrence of inflammation.